ANALISIS PENGARUH HARGA DAN PROMOSI TERHADAP PENINGKATAN PENJUALAN TIKET PADA PT. ARCA PERKASA TOUR & TRAVEL DI MAKASSAR - Fitri Indah Sari M (Jurnal Bisnis dan Kewirausahaan, 2015)
The main problem in this study is whether the pricing and promotion affect the volume of ticket sales PT. Arca Perkasa Tour & Travel in Makassar.The purpose of this study was to determine the extent of the effect of price and promotion to increase the volume of ticket sales at PT. Arca Perkasa Tour & Travel in Makassar. To analyze the relationship and the effect of price and promotion to increase the volume of ticket sales at PT. Arca Perkasa Tour & Travel in Makassar.For the purpose of applying the descriptive method is used, the method of multiple linear regression analysis, Based on the results of the regression analysis obtained by the equation Y = 1690.966 to 0.708 X1 + 0.456 X2 where bᴼ = 1690.966 is a constant value, in other words if the selling price and promotion costs do not change the value of the ticket sales amounted to 1690.966 sheet b1x1 = -0.708, which means when the selling price (X1) increased by Rp. 100,000 per sheet, the effect on the volume of ticket sales will decrease by 0.708% b2X2 = 0.458 which means that if the cost of the promotion (X2) increased by Rp. 100,000 then the effect on the volume of sales will increase by Rp. 0.458%.